A meta-analysis of topiroxostat for the treatment of chronic kidney disease with hyperuricemia - ZHANG Zhi-qin; ZHANG Lian; ZHA Dong-qing; HU Chun; WANG Rui; WU Xiao-yan (Linchuang shenzangbing zazhi)
Objective To conduct a meta-analysis of the effectiveness and safety of to puroxostat for treatment of chronic kidney disease with hyperuricemia（HUA）.Methods Studies on the treatment of CKD with HUA with topiroxostat were retrieved from Pubmed,Embase,Cochrane Library,Web of Science,biomedical literature database,Wanfang and Viper databases from the time of establishment to March 2020.The included randomized controlled trials were meta-analyzed using RevMan5.3 software.Results A total of 7 randomized controlled trials were included.Meta-analysis showed that in chronic kidney disease with hyperuricemia,Topiroxostat had a significant uric acid-lowering effect in both dialysis and non-dialysis chronic kidney disease.However,there was no significant difference between to piroxostat and febuxostat in lowering uric acid.There were no significant differences in glomerular filtration rate,systolic blood pressure,diastolic blood pressure,or incidence of adverse events between topiroxostat and placebo,but the urinary protein positive rate was reduced for topiroxostat.Conclusions Topiroxostat can reduce the serum uric acid level in chronic kidney with hyperuricemia,and the positive rate of urinary albumin was lower than that in the control group.However,there is no statistical difference in the short-term renal protective effect and vascular protective effect between topiroxostat and placebo.